(3MGTjI eYGde GdOjfs - (3GdYGedj, GdehShj, fhQ GdOjf, Ydj Hf CHj GdMSf Ydj Hf GdMSjf, J (B1068(3g`s ((3eMeO Hf CMeO Hf Ydj Hf CMeO GdMQjQj GdMQahTjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3hHYO agPg ahGFO TQjaI (B... (3YdbgG GdCSJGP(B... (3Ydi HYV ehGVY ef eYGde GdOjf dCNjg(B... (3bGd(B: (3abGd hgd jSCd GdfGS Yf TjA CaVd ef GdMdGd hGdMQGe(B...s
(3BNQgG (B:s
(3dCf GSJYeGd HYV GdCdaGX HeYfi HYV dG jhLH GJMGOgeG aj GdeYfi(B. (3GdMeO ddg Ydi GdJeGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI HQbe(B: 995s
(3GdPQjYI HQbe(B: 995s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs